Do In-Prison Correctional Programs Affect Postrelease Employment and Earnings? - Jensen, Eric (International journal of offender therapy and comparative criminology, 2020)
The objective of this research is to examine the effects of general educational development (GED) attainment in prison and therapeutic community participation on postrelease employment and earnings. The participants are all males released from prisons in Idaho during 2004. The dependent variables are employment and mean quarterly earnings up to 57 months after release. Propensity score matching analysis was used to enhance the equivalence of the comparison groups, with a small percentage of overly influential observations trimmed. Logistic regression was used to examine the effects of programming on employment. GED had no effect on employment. The effect of therapeutic community approached significance. The statistical analyses on earnings used generalized linear models based on the gamma distribution due to the highly skewed distribution of this variable. These analyses found that GED had no effect on earnings and that participation in a therapeutic community had a highly significant effect on mean quarterly earnings.